2011
DOI: 10.1039/c0ce00413h
|View full text |Cite
|
Sign up to set email alerts
|

Molten salt synthesis of K4Nb6O17, K2Nb4O11and KNb3O8crystals with needle- or plate-like morphology

Abstract: Here we report on molten salt synthesis of four different compounds in the K 2 O-Na 2 O-Nb 2 O 5 system. The three compounds K 4 Nb 6 O 17 , K 2 Nb 4 O 11 and KNb 3 O 8 , with non-cubic crystal structures, were prepared as single crystalline particles with large aspect ratios. K 4 Nb 6 O 17 was prepared with a platelike morphology, K 2 Nb 4 O 11 a fibre-like and finally KNb 3 O 8 had a plate like morphology. K x Na 1Àx NbO 3 , with a cubic perovskite crystal structure at the synthesis conditions, was only obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…The C sites form narrow triangular channels, and are usually vacant, as only a few cations such as Li + and Nb 5+ are small enough for these sites. 8,9 The B1 and B2 sites are symmetrically different While PN and SBN are similar in terms of structure, there are fundamental differences in the behaviour of the two compounds. PN is a classical ferroelectric, while SBN is ferroelectric for barium-rich compositions, but becomes relaxor-like for strontium contents higher than approximately x = 0.6.…”
Section: Introductionmentioning
confidence: 99%
“…The C sites form narrow triangular channels, and are usually vacant, as only a few cations such as Li + and Nb 5+ are small enough for these sites. 8,9 The B1 and B2 sites are symmetrically different While PN and SBN are similar in terms of structure, there are fundamental differences in the behaviour of the two compounds. PN is a classical ferroelectric, while SBN is ferroelectric for barium-rich compositions, but becomes relaxor-like for strontium contents higher than approximately x = 0.6.…”
Section: Introductionmentioning
confidence: 99%
“…2b-d) as a result of the mixed NbO 6 -and TaO 6 -octahedra, lowering the total interfacial energy and leading to anisotropic growth. As suggested by Madaro et al, 31 the connectivity of octahedra can determine the aspect ratio of the crystals. The ultraviolet-visible (UV-Vis) diffuse reflectance spectra of Ba 5 Nb 4−x Ta x O 15 crystals are plotted in Fig.…”
Section: Atoms/positionsmentioning
confidence: 99%
“…25,28,29 The cation exchange allows to reach new properties consecutive to the reaction between the host matrix Nb 3 and electrochemical performances 25 that are attractive as anode active materials for sodium-ion battery. 33 Several routes have been used to synthesize KNb 3 O 8 as single crystal by Czochralski and Bridgman-type methods, 34 and as powder by solid state chemistry, 5,35 molten salts synthesis, 35,36 hydrothermal synthesis, synthesis. 39 In polycrystalline materials, it was reported that the KNb 3 O 8 particles have an elongated plate-like or wire-like morphology.…”
Section: 21-27mentioning
confidence: 99%
“…39 In polycrystalline materials, it was reported that the KNb 3 O 8 particles have an elongated plate-like or wire-like morphology. 10,35,40,41 In reason of this particular morphology, wire-like KNb 3 O 8 was used as precursor to obtain by topochemical methods low-dimensional Nb 2 O 5 crystals that are of interest for catalysis. [42][43][44] So far, no synthesis of the KNb 3 O 8 phase as lm or coating has been reported.…”
Section: 21-27mentioning
confidence: 99%
See 1 more Smart Citation